The job dispatch control policy for production lines with overlapped time window constraints and constant processing times - Hu, Wei (Nanyang Technological University, 2020)
With the development of today’s market demands, the production lines become more and more complexed, manufacturers face more problems including high quality, product mix, and time constraints. It is well known that computing the exact cycle time becomes very complex when there are overlapped time window constraints in the production line(an NP-hard problem), as it involves managing the production process across multiple lots, They also ignore the possibility of lots having different routes through the manufacturing. In this thesis, we use the reduction method to simplify the simulation system and then propose a dispatch control policy based on simulation results. Chapter 1 and chapter 2 are the introduction and the literature review, respectively. In chapter 3, we mainly introduced digital twin, reduction method and our optimization method of simulation. In chapter 4, we discussed the details of the simulate experiments and analyzed the results. Firstly, the accuracy of the system and the correctness of the reduction method was verified, and then the performance of the reduction method in the case of overlapped time constraints and multiple parts was explored. Finally, the variation of deviation with utilization and variability was analyzed. The dispatch control policy and conclusions were presented in Chapter 5 and Chapter 6. The major contributions of our study are as follows: 1. The job dispatch control policy gives a reasonable estimate for the cycle time. This estimate is used to reduce rework or scrap by avoiding the violation of time constraints. 2. The simulation has a short run time (only a few seconds for the problem sizes considered in the study), and hence can be re-run immediately when a machine breaks down. Key Words: Overlapped Time Constraints; Multiple Parts; Simulation Reduction Method; Dispatch Control Policy